The Role of Citizenship Education in the Process of Forming the National Identity of the Indonesian Nation - Dadang Mulyana (Sean Institute, 2024)
National identity is an integral aspect in building unity and diversity in a country. Citizenship education is considered a key instrument in strengthening and developing awareness of national identity among the younger generation. This research aims to explore and analyze the role of citizenship education in forming the national identity of the Indonesian nation. This research uses a qualitative approach with descriptive methods. The research results show that citizenship education has a significant impact in shaping the national identity and character of Indonesian citizens. Through the implementation of a curriculum that focuses on understanding the values of Pancasila, democratic principles, cultural diversity, as well as Indonesia's history and natural wealth, students are able to develop a sense of national awareness, tolerance, and be critical of social and political issues. Citizenship education has also succeeded in fostering a sense of love and pride for the homeland, which is an important factor in strengthening Indonesia's national identity. Therefore, the results of this research provide empirical support for the vital role of citizenship education in shaping the character and national identity of students in Indonesia.